2018
DOI: 10.3389/fphys.2018.00433
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish Self-Administer Amphetamine in a Spatially Contingent Task

Abstract: Natural reward is an essential element of any organism’s ability to adapt to environmental variation. Its underlying circuits and mechanisms guide the learning process as they help associate an event, or cue, with the perception of an outcome’s value. More generally, natural reward serves as the fundamental generator of all motivated behavior. Addictive plant alkaloids are able to activate this circuitry in taxa ranging from planaria to humans. With modularly organized nervous systems and confirmed vulnerabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Crayfish species are widely distributed, worldwide, in natural environments (https://en.wikipedia.org/wiki/Crayfish). Subjects for use in laboratory experiments can be purchased from pet stores (as we did for some of our subjects), biological suppliers (Swierzbinski and Herberholz, 2018; Teshiba et al, 2001), or are easily fished from the wild, if locally available (Datta et al, 2018; Imeh-Nathaniel et al, 2017). This invertebrate species can be used for research within institutions that do not maintain regulatory approvals and facilities appropriate for vertebrate animal research subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crayfish species are widely distributed, worldwide, in natural environments (https://en.wikipedia.org/wiki/Crayfish). Subjects for use in laboratory experiments can be purchased from pet stores (as we did for some of our subjects), biological suppliers (Swierzbinski and Herberholz, 2018; Teshiba et al, 2001), or are easily fished from the wild, if locally available (Datta et al, 2018; Imeh-Nathaniel et al, 2017). This invertebrate species can be used for research within institutions that do not maintain regulatory approvals and facilities appropriate for vertebrate animal research subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of papers have shown that crayfish can be used to assess the effects of ethanol on neurotransmission (Swierzbinski et al, 2017) and behavioral effects of other abused drugs, including locomotor responses to intravenous cocaine, morphine and methamphetamine (Imeh-Nathaniel et al, 2017) and the intravenous self-administration of amphetamine (Datta et al, 2018). Furthermore, crayfish are a popular electrophysiology model for introductory neuroscience laboratory classes (Cooper et al, 2011; Ewing and Medler, 2020; Land et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Robust bias for the associated sensory environment arose when it was paired with infusions of amphetamine, cocaine, methamphetamine, and opioids [Panksepp and Huber, 2004;Nathaniel et al, 2010;Imeh-Nathaniel et al, 2016]. Drug self-administration has been reported in roundworms with cocaine, nicotine, and methamphetamine [Engleman et al, 2018] and in crayfish with amphetamine [Datta et al, 2018]. Invertebrate models also exhibit strong tendencies for relapse after prolonged periods of abstinence [Nathaniel et al, 2009].…”
Section: Doi: 101159/000517121mentioning
confidence: 99%
“…The need to assess and remember contingencies has shaped behavioral responses since the mechanisms for learning and memory organization emerged in a longdistant evolutionary past. The extent to which crayfish can adjust their choices based on consequences was explored in a spatially explicit paradigm, where environmental cues (e.g., tactile and visual) in an arena were paired with either mild electric shock (punishment; Bhimani & Huber, 2015) or psychostimulant administration (reward; Datta, van Staaden, & Huber, 2018). Heat maps summarizing space utilization in the punishment experiments (see Figure 3) reveal that crayfish quickly learned to avoid shock-paired substrates, and confined themselves to the "safe" substrate (see Figures 3b and c).…”
Section: Operant Learningmentioning
confidence: 99%
“…In this spatially contingent version of a self-administration paradigm, enhanced operant responding indicates that the drug acts as an effective reinforcer of behavioral choices. Furthermore, crayfish more readily learned to self-administer amphetamine when drug was delivered directly to the brain, rather than systemically (Datta et al, 2018).…”
Section: Operant Learningmentioning
confidence: 99%